Involvement Degree of Women in the Buying Decision of Saudi Family - Al-Nsour, Iyad (The Arab Journal of Administration, 2018)
This study aimed at determining and measuring effect of involving the women on the buying decision of Saudi family, as well as determining the statistical differences in the involvement degree, the buying roles and the buying criteria used in buying process by Saudi women. To achieve the research objectives, the pilot study was conducted. The study population consisted of all Saudi females living in city of Riyadh estimated at 2.2 millions in year of 2016. The sample was calculated by 387 of Saudi females, and simple random sample was used. The study showed that there is a significant statistical effect of involving the women on the buying decision of Saudi family, and also it was showed that there are a statistical differences in the buying roles according to years of marriage and number of sons in the Saudi family, but there are no statistical differences in both of the involvement degree and the buying criteria used in buying process by Saudi women. Finally, the study recommended a set of marketing implications and suggestions that help the producers and advertisers to design their advertisements, products and stores in a way that take the interests, psychological and personal needs of Saudi women in their consecrations.